2023
DOI: 10.1128/aac.01428-22
|View full text |Cite
|
Sign up to set email alerts
|

Killing Two Birds with One Stone: Discovery of Dual Inhibitors of Oxygen and Fumarate Respiration in Zoonotic Parasite, Echinococcus multilocularis

Abstract: Ascofuranone (AF), a meroterpenoid isolated from various filamentous fungi, including Acremonium egyptiacum , has been reported as a potential lead candidate for drug development against parasites and cancer. In this study, we demonstrated that AF and its derivatives are potent anthelminthic agents, particularly against Echinococcus multilocularis , which is the causative agent of alveolar echinococcosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It is worth mentioning that the inhibition of NADH-fumarate reductase by ascochlorin was more pronounced than expected ( Table 2 ). A recent study ( Enkai et al., 2023 ) showed that ascofuranone, an analog of ascochlorin, effectively inhibited complex II of E. multilocularis . These results suggest that ascochlorin analogs may inhibit complex II of parasitic platyhelminths.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is worth mentioning that the inhibition of NADH-fumarate reductase by ascochlorin was more pronounced than expected ( Table 2 ). A recent study ( Enkai et al., 2023 ) showed that ascofuranone, an analog of ascochlorin, effectively inhibited complex II of E. multilocularis . These results suggest that ascochlorin analogs may inhibit complex II of parasitic platyhelminths.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of complex I by rotenone also affected fumarate respiration and killed NEJs ( Figure 4 ). An unexpected effect of ascochlorin on NEJs under the anaerobic conditions ( Figure 4 ) was probably due to its inhibitory activity against complex II (72.3%) ( Table 2 ) ( Enkai et al., 2023 ). The present study revealed that NEJs can use both oxygen and fumarate respiration ( Figure 1 ), depending on oxygen availability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations